Synthesis of Collidine from Dinitrogen via a Tungsten Nitride - Eberle, Lukas; Ballmann, Joachim (Journal of the American Chemical Society, 2024)
The synthesis of pyridines from dinitrogen in homogeneous solution is known to be challenging considering that an N2 cleavage step needs to be combined with two N-C coupling steps. Herein, a tungsten complex bearing a tailor-made 2,2′-(tBu2As)2-substituted tolane ligand scaffold was shown to split N2 to afford the corresponding tungsten nitride, which is not the case for the corresponding (iPr2As)2-substituted derivative. The former nitride was then reacted with 2,4,6-trimethylpyrylium triflate, which led to the formation of a tungsten oxo complex, along with collidine. Over the course of this reaction, the O atom of the pyrylium starting material was replaced with an N atom via a hitherto unprecedented skeletal editing process.